Avaliação da influência do exercício físico regular na modulação do sistema imunológico de camundongos infectados com Toxoplasma Gondii - Bortolini, Miguel Junior Sordi (2014)
Physical exercise has been implicated in several immunophysiological improvements especially during the aging process when an immunocompromised status could be established. Toxoplasma gondii is a protozoan parasite that causes a widespread opportunistic infection, which may present severe consequences, particularly to the fetus and immunocompromised patients. It is estimated that one-third of the human population worldwide has been infected by this parasite, being the reactivation during immunesenescence an unexplored public health issue. The present study was designed to assess the immunophysiological differences between exercised versus sedentary C57BL/6 male mice that have been infected by T. gondii. Before the two key set of experiments, several other sets were carried out to the prospection of the main found data of this study. There were two main sets of experiments: in the first set, the animals were infected after exercising and three groups were formed: experimental groups - infected sedentary (IS, n=6); infected exercised (IEx, n=6) and control group - non-infected sedentary (NIS, n=6). When splenocytes were stimulated by T. gondii-soluble tachyzoite antigens, it was found an significant increasing (P<0.0001) in interferon-gamma (IFN-) production concomitant with any changes in IL-10, allowing a greater IFN-/IL-10 ratios, produced by the cells from exercised group compared to sedentary one. However, there was no difference concerning quantification of T. gondii genomic DNA by qPCR and immunohistochemistry analysis in brain cysts (P>0.05). In order to further investigate the consequences of these data for the host, a second set of experiments was performed, when the animals were infected before exercising and four groups of animals were established for comparison purpose, as follows: experimental groups - infected sedentary (IS, n=7); infected exercised (IEx, n=6) and control groups - non-infected sedentary (NIS, n=6) and non-infected exercised (NIEx, n=6). It was found that exercised group survived longer (P<0.05) than sedentary one. In both sets of experiments, mice have been submitted to moderate exercises: running (14m/min; 3x/week) and strength (60-80% of one-repetition maximum; 2x/week). In summary, moderated aerobic and strength exercises are able to modulate immune responses against T. gondii infection, being these immunological features beneficial to the host.